Telaah Kritis terhadap Argumen Mayoritas Ulama tentang Nasab Anak Zina - Muhammad Muhammad (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2020)
he lineage of the children of adultery as agreed by religious scholars (‘ulamā’) and Indonesian Ulama Council (MUI) is ascribed to the mother, not the father. This is due to the unclarity of the marital bond between the woman and the man who conduct adultery, and due to the uncertainty of sperms that fertilize the ovum (egg cell) of a woman. Consequently, the children of adultery become exiled and marginalized in society, bearing mistakes of their ‘parents’. In fact, Islam has emphasized that every child born is essentially chaste. If the child born from adultery is ascribed to the mother, he/she does not have whatever rights from the father. Therefore, it is important to review the question regarding the lineage of the children of adultery, in order to determine the future of the children. Based on the literature research with critical analysis method, this article argues that the children of adultery remain to be biologically ascribed to the father together with their rights from the latter. The children born from adultery do not bear the mistakes of their ‘parents.’ In the contemporary era, to determine the children lineage can use such a tool as DNA test that is believed as accurate.